2012
DOI: 10.1016/j.fob.2012.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin induces autophagy and inhibits the growth of iron‐loaded human myeloid leukemia K562 cells via ROS toxicity

Abstract: Highlights► DHA induced K562 cells autophagy followed by LC3-II protein expression. ► The DHA-induced autophagy might be ROS dependent. ► Inhibition of K562 cell proliferation by DHA was also dependent upon iron decrease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 38 publications
2
39
0
1
Order By: Relevance
“…Indeed, one recent report showed that ART induces autophagy via up-regulation of Beclin 1 expression (16). Moreover, our findings are consistent with three other reports suggesting that DHA was able to induce autophagy in cancer cells (57)(58)(59). DHA is a derivative of artemisinin, with a mechanistic action similar to that of ART (50,60).…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, one recent report showed that ART induces autophagy via up-regulation of Beclin 1 expression (16). Moreover, our findings are consistent with three other reports suggesting that DHA was able to induce autophagy in cancer cells (57)(58)(59). DHA is a derivative of artemisinin, with a mechanistic action similar to that of ART (50,60).…”
Section: Discussionsupporting
confidence: 93%
“…It has been established that cancer cells produce higher levels of ROS than those of normal cells, as a result of metabolic stress and proliferative requirements. A previous study reported that DHA induced autophagy in the mitochondria of leukemia K562 cells (31). A further study found that the sensitivity of cancer cells to artemisinin was attenuated following the overexpression of oxidative stress associated enzymes (32).…”
Section: Discussionmentioning
confidence: 92%
“…The results of the present study suggest that treatment with dihydroartemisinin significantly suppressed PARP levels in HCT116 cell. Wang et al (19) reported that dihydroartemisinin inhibits the growth and induces autophagy of iron-loaded human myeloid leukemia via PARP expression. These results suggest that transactivated PARP, caspase-3/9 and BAX each serve a role in dihydroartemisinin-induced apoptosis in CRC cells.…”
Section: Discussionmentioning
confidence: 99%